Social Exclusion Shifts Personal Network Scope - Bayer, Joseph B.; Hauser, David J.; Shah, Kinari M.; O’Donnell, Matthew Brook; Falk, Emily B. (Frontiers in Psychology, 2019)
Social exclusion has the potential to alter subsequent social interactions with the members of personal networks, especially given their online availability in contemporary life. Nonetheless, there is minimal research examining how social challenges such as exclusion alter ensuing interactions with personal networks. Here, we tested whether being excluded during a social interaction altered which personal ties are most salient in a subsequent, ostensibly unrelated, online news sharing task. Across three operationalizations of tie strength, exclusion (vs. inclusion) increased sharing to close friends, but (unexpectedly) decreased sharing to close family members. The findings provide preliminary evidence that negative encounters may shift attention toward certain types of network ties and away from others. Future work is needed to examine how social experiences influence personal network scope – i.e., who comes to mind – in the background of daily life.